Adoption of Monthly Rent Payment Structure in Lagos State: Benefits and Challenges - Oluwunmi, A. O.; Olawale-Olonode, W. E. (International Journal of Real Estate, 2025)
Tenants in Nigeria and many other developing countries are usually required to pay rent upfront and in full for a period of one to two years. Tenants may find this challenging, especially if they have limited resources. Hence, this study investigated the benefits and challenges of adopting a monthly rent payment system in Lagos. A total of 94 respondents completed the e-questionnaire used to gather data which was analysed using a relative importance index and ANOVA. The results indicate that monthly rent payment will help tenants to better manage their finances, make rent more affordable, and promote extended tenancy. It was found that the biggest barriers to the adoption of monthly payment are opposition from landlords, and the lack of a facilitating legal framework. The study advised policymakers to develop legal frameworks that protect the interests of both tenants and landlords under a monthly rent payment system, coupled with awareness campaigns to aid better understanding of the benefits of monthly payments.